The correspondence - Daniels, J. D., 1974- (Farrar, Straus and Giroux, 2017)
"The first collection from a Whiting Writers' Award winner whose work has become a fixture of The Paris Review and n+1. Can civilization save us from ourselves? That is the question J. D. Daniels asks in his first book, a series of six letters written during dark nights of the soul. Working from his own highly varied experience--as a janitor, a night watchman, an adjunct professor, a drunk, an exterminator, a dutiful son--he considers how far books and learning and psychoanalysis can get us, and how muchwe're stuck in the mud. In prose wound as tight as a copper spring, Daniels takes us from the highways of his native Kentucky to the Balearic Islands and from the Pampas of Brazil to the rarefied precincts of Cambridge, Massachusetts. His traveling companions include psychotic kindergarten teachers, Israeli sailors, and Southern Baptists on fire for Christ. In each dispatch, Daniels takes risks--not just literary (voice, tone, form) but also more immediate, such as spending two years on a Brazilian jujitsu team (he gets beaten to a pulp, repeatedly) or participating in group psychoanalysis (where he goes temporarily insane). Daniels is that rare thing, a writer completely in earnest whose wit never deserts him, even in extremis. Inventive, intimate, restless, streetwise, and erudite, The Correspondence introduces a brave and original observer of the inner life under pressure. A collection of the author's essays, previously published in The Paris Review"--